Alibangbang in captivity Life stories of male homosexual prisoners in the leyte regional prison, Abuyog, Leyte. - Agustin, Zoreen E., et al; Mercines, Monique I.; Relis, Leonel J. (Zoreen E. Agustin, 2013)
Out of the chrysalis of discrimination, male homosexuals enjoy the emancipation associated with their acceptance of their sexuality; however, some of them are locked up behind bars because of the criminal liabilities they face. A qualitative study on the life stories of male homosexual prisoners in the Leyte Regional Prison in Abuyog, Leyte was conducted to explore the relevance of their sexuality with transgression of the law and their imprisonment as well as to understand their life experiences. Being a male homosexual prisoner presents several hardships and struggles, but being one does not make an individual a captive of misery, instead, one still continues to find meaning in his life and at the same time hope to gain full acceptance and respect from the society. A triangulation process was conducted through interviews with six (n=6) male homosexual prisoners and their close inmates and an analysis of the participants' profile at the LRP. The life stories of the participants can provide them with the opportunity to be heard and the institution tasked to guide these prisoners can integrate inputs to come up with a more holistic understanding of this segment of the population which will help facilitate future programs to promote the wellbeing of male homosexual prisoners.